2022
DOI: 10.3390/s22031069
|View full text |Cite
|
Sign up to set email alerts
|

Torque Ripple Suppression of Brushless DC Motor Drive System Based on Improved Harmonic Injection Active Disturbance Rejection Control

Abstract: The positioning accuracy and speed stability of the brushless DC motor (BLDC motor), as the drive element of the optomechanically scanned system (OMSS), are closely interrelated to the final imaging quality of the system. Active disturbance rejection control (ADRC) with strong anti-interference ability, fast response and good robustness is one of the extensively used control strategies. However, the performance of ADRC working in a complicated environment will be limited due to the controller structure, parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…It has powerful anti-interference capabilities, a quick reaction, and excellent resilience. The parameters of an upgraded ADRC are adjusted using an SMA based on a Levy flight operator (LF-SMA) [ 60 ]. The ADRC that has been proposed is stable, according to the Lyapunov stability theory.…”
Section: Methods Of Smamentioning
confidence: 99%
“…It has powerful anti-interference capabilities, a quick reaction, and excellent resilience. The parameters of an upgraded ADRC are adjusted using an SMA based on a Levy flight operator (LF-SMA) [ 60 ]. The ADRC that has been proposed is stable, according to the Lyapunov stability theory.…”
Section: Methods Of Smamentioning
confidence: 99%
“…Due to limited resolution, misalignment, electrical noise, and physical vibration, both phase advance and commutation pulse controls need the employment of a sequencing algorithm based on a Hall effect sensor signal, which has poor precision. [29][30][31].…”
Section: Literature Reviewmentioning
confidence: 99%
“…e roots of torque ripple in the BLDCM in the speed closed-loop state were investigated [30], and a novel PWM-MPC method was suggested that computed the duty cycle of the power switches during the commutation period using the predictive model, but the proposed method worked well only at lower or higher speed ranges only. Because of its superior performance in positioning and torque ripple reduction, field oriented control (FOC) is used in BLDC motor drive systems [31]. However, effective performance necessitates precise control system state monitoring, which is frequently attributed to superior sensors.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The approach in [26] discussed the use of an enhanced self-immunity controller to reduce torque pulsation in BLDC. The approach in [27] details the implementation of ADRC in a flywheel storage system to improve its immunity and dynamic characteristics.…”
Section: Introductionmentioning
confidence: 99%